Effect of Organic Fertilizers on Yield Components of Some Tomato Cultivar - Paksoy, M.; Acar, B. (Asian Journal of Chemistry, 2010)
The aim of the study was to determine the effects of organic fertilizers on yield components in furrow irrigated some tomato cultivars in Konya, Turkey. As plant materials; H-2274, Olga F1, Abundance, V-200 F1, Topkapi F1, ACN-55 F1, ACN-112 F1, Porsuk F1, H-12-63-208 F1 and ACN-90 F1 tomato cultivars were used. Two different organic fertilizers namely organic mineral fertilizer (OMF) (1 t ha-1) and farmyard manure (10 t ha-1) were applied to soil before planting. In results, the highest yield, fruit number, mean fruit weight, fruit size, fruit height, total soluble solid (TSS) were obtained from ACN-55 F1 (86.161 t ha-1) and H-2274 (76.771 t ha-1); H-2274 (1473.3 number ha-1) and ACN-55 F1 (1578.9 number ha-1); ACN-112 F1 (100.92 g) and Porsuk F1 (102.33 g); ACN- 112 F1 (7.42 cm) and Porsuk F1 (7.08 cm); ACN-112 F1 (6.48 cm) and H-12-63-208 F1 (6.65 cm) and H-2274 (5.78 %) and H-12-63-208 F1 (5.52 %), respectively. The mean fruit weight was found higher in farmyard manure applied plots (84.01 g) than control.